2015
DOI: 10.1891/2158-0782.6.2.75
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Increased Skin-to-Skin Contact With the Mother in Breastfeeding Neonates on Exclusive Breastfeeding at 4 and 8 Weeks Postpartum

Abstract: Objective: To evaluate dose of skin-to-skin (STS) contact as a nursing intervention to increase the rate of exclusive breastfeeding after dischargeDesign: A descriptive correlational studySetting: A Level II maternity unit in OhioParticipants: Women who had a vaginal delivery of a term, well newborn, with intent to exclusively breastfeedMethods: Newborns were placed STS with their mothers at birth. Mothers were encouraged to maintain frequent STS with their newborns while in the hospital, and kept a log of STS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The evidence shows that SSC is an accessible practice promoting breastfeeding during the neonatal period [2,5,18], protecting against infections and future allergies [16,19]. Breastfeeding promotes increased blood circulation and temperature in the breast area, promoting breast milk production and helping keep the newborn infant warm [3,5].…”
Section: Skin-to-skin Contact and Breastfeeding And Eating Behaviorsmentioning
confidence: 99%
See 3 more Smart Citations
“…The evidence shows that SSC is an accessible practice promoting breastfeeding during the neonatal period [2,5,18], protecting against infections and future allergies [16,19]. Breastfeeding promotes increased blood circulation and temperature in the breast area, promoting breast milk production and helping keep the newborn infant warm [3,5].…”
Section: Skin-to-skin Contact and Breastfeeding And Eating Behaviorsmentioning
confidence: 99%
“…After birth, the newborn infant experiences a sensitive period that enhances positive behaviors development beyond the first day of life [2,5,18]. Furthermore, researchers found that SSC promotes psychosocial health, increasing the infant's perception as an active agent in social interactions in her surrounding space [18].…”
Section: Skin-to-skin Contact and Psychosocial Health And Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The varied benefits followed by SSC include the enhancement of autonomic nervous system development, maintenance of infants' physiological stability, and increase of immunity (Butruille et al, 2017;Feldman & Eidelman, 2003). Further benefits are optimization of breastfeeding (Ruxer et al, 2015), facilitation of the parent-infant bonding (Tessier et al, 1998), and mitigation of infants' traumatic experiences in the NICU associated with stress and pain responses (Eliades, 2018;Feldman et al, 2014). A Cochrane review of SSC and neonatal outcomes included 21 randomized controlled trials (RCTs) (n=3042 infants) and presented consistent beneficial effects across a variety of outcomes (Conde-Agudelo & Díaz-Rossello, 2016).…”
Section: Skin To Skin Carementioning
confidence: 99%